Echocardiographic predictors of low risk haemodynamic parameters in patients with pulmonary arterial hypertension. (14th October 2021) - Rotunno, M; Dardi, F; Palazzini, M; Guarino, D; Zuffa, E; Magnani, I; De Lorenzis, A; Ballerini, A; Manes, A; Galie, N
Abstract: Background: A periodic and multiparametric assessment of the risk profile of patients with pulmonary arterial hypertension (PAH) is essential for a low-risk oriented treatment strategy. Haemodynamic parameters anyway cannot be collected at each scheduled outpatients clinic follow-up visit. Purpose: To evaluate echocardiographic predictors of haemodynamic low-risk parameters in patients with PAH. Methods: Patients with PAH referred to our centre were included up to 31 December 2019. All patients underwent baseline demographic, clinical, WHO functional class, 6-minute walk test, brain natriuretic peptide (BNP), right cardiac catheterization and echocardiographic evaluation. Through a multivariate logistic regression analysis we evaluate the echocardiographic predictors of low risk for: 1) BNP/right atrial pressure (RAP): NT-proBNP <300 ng/l/BNP <50 ng/l AND RAP <8 mmHg; 2) cardiac index (CI)/mixed venous oxygen saturation (SvO2): CI ≥2.5 l/min/m 2 AND SvO2 >65%. Echocardiographic parameters cut-offs were chosen on the basis of the ROC curves or Literature data. Results: 1020 patients were included. The two analysis were performed independently. 1. Independent echocardiographic predictors of low-risk BNP/RAP were: indexed right atrial area, mitral E/A ratio, dimension and inspiratory collapse of inferior vena cava and indexed left ventricular diastolic volume. We elaborated a score utilizing these parameter cut-offs: an indexed right atrial area of 10.4–15 cm 2 /m 2, a mitral E/A ratio of 0.8, dimension and inspiratory collapse of inferior vena cava indicative of 0–5 vs 5–10 vs 10–20 mmHg and an indexed left ventricular diastolic volume of 32 ml/m 2 . The score has AUC: 0.62, specificity: 92%, sensitivity: 33%, negative predictive value: 70%, positive predictive value: 69%. 2. Independent echocardiographic predictors of low-risk CI/SvO2 were: S wave at TDI, Tei index, tricuspid annular plane systolic excursion (TAPSE), indexed left ventricular diastolic volume and the severity of the tricuspid regurgitation. We elaborated a score utilizing these parameter cut-offs: an S wave at TDI of 9.5 cm/s, a Tei index of 0.4, a TAPSE of 1.7 cm, an indexed left ventricular diastolic volume of 32 ml/m 2 and a mild vs more than mild tricuspid regurgitation. The score has AUC: 0.70, specificity: 89%, sensitivity: 50%, negative predictive value: 71%, positive predictive value: 77%. Conclusion: Echocardiographic parameters can be used to rule out the presence of low-risk BNP/RAP values (indexed right atrial area, mitral E/A ratio, dimension and inspiratory collapse of inferior vena cava and indexed left ventricular diastolic volume) and low-risk CI/SvO2 (S wave at TDI, Tei index, TAPSE, indexed left ventricular diastolic volume and severity of tricuspid regurgitation). Funding Acknowledgement: Type of funding sources: None.